PENGARUH E-SERVICE QUALITY TERHADAP E-LOYALTY (Survei pada Nasabah Mobile Banking Mandiri di Indonesia ) - Auliana Destiana Wahyu, - (2019)
The development of communication technology in Indonesia has an impact on consumer attitudes towards products / services that change traditional consumer behavior to online consumer behavior called e-loyalty. Quality of online services in marketing can influence consumer behavior on online services as a positive attitude towards customers of electronic business. Solutions that can be done by banking companies in Indonesia in order to increase e-loyalty by increasing e-service quality. This study aims to find the effect of e-service quality on e-loyalty. The type of research used is descriptive and ve rification. The sampling technique used in this study was non-probability sampling using a purposive method. The data analysis technique used is path analysis with SPSS 22.0 for Windows. The findings of this study indicate that the e-service quality in the category is quite good, the description of e-loyalty in the medium category. The e-service quality variable that has the highest score on e-loyalty is the privacy dimension, while the variable that has the lowest score is fulfillment. Dimensions that have an influence on e-loyalty are efficiency, system availability and privacy. Based on the results of this study, it is suggested in e-service quality companies to increase fulfillment in order to increase e-loyalty. It is hoped that e-service quality can be further considered by companies in the banking industry in increasing corporate e-loyalty. Keyword Mobile Banking, E-Setvice Quality, Effeciency, Fulfillment, System Availability, Privacy, E-Loyalty